The Memoirs of General Grivas - Grivas, General, 1898-1974; Edited by Foley, Charles (London Longmans, Green and Co. Ltd., 1964)
The memoirs of General George Grivas, in which he describes his role as the leader of an anti-colonial guerrilla force against Britain on the island of Cyprus.
Include Illustrations, Appendices and Index.
Georgios Grivas (1897 - 1974) was a Cyprus-born general in the Greek Army, leader of the EOKA guerrilla organization and EOKA B paramilitary organization.
Keywords: Cyprus -- Cyprus -- History